The Integrated Development Index (I-Dex): a new comprehensive approach to measuring human development - Mohd Amin, Ruzita; Abdullah Yusof, Selamah; Haneef, Mohamed Aslam; Mohammed, Mustafa Omar; Oziev, Gapur (Bloomsbury Qatar Foundation, 2015)
Standard economics and policy prescriptions adopt the modernization thesis as its base, which says that developing countries can modernize by undergoing secularization and westernization. However, Muslim countries, including Malaysia, have shown that more economic development and progress can take place together with a renewed manifestation of Islamic values and norms. This important departure from the modernization thesis reflects a potential alternative transformational development model. However, conceptual and theoretical frameworks of this alternative development model are still lacking. There is an urgent need for Muslim countries to develop this alternative model, which represents a more holistic and inclusive concept of development that integrates the physical/material, intellectual and spiritual dimensions of human beings. This study proposes to develop an integrated Islamic development framework and index based on, and representing, the Maqasid al-Shariah or noble objectives of the Shariah for OIC and non-OIC countries. The final expected outcome of this study is a Maqasid-based Integrated Development Index (I-Dex) that will better represent holistic development and well-being according to Islamic benchmarks, hence providing academics, students and policymakers in Muslim countries with an alternative measurement of progress.